Maternal and neonatal factors associated with low birth weight among neonates delivered at the University of Gondar comprehensive specialized hospital, Northwest Ethiopia - Adugna, Dagnew Getnet; Worku, Misganaw Gebrie (Frontiers in Pediatrics, 2022)
Abstract Introduction: Low birth weight is a major underlying contributor to neonatal and infant mortality. Although low birth weight remains an important public health problem in Ethiopia, little emphasis is paid to its intervention as a means of reducing neonatal mortality. The study aimed to assess the magnitude of low birth weight and its associated factors among newborns delivered at the University of Gondar comprehensive specialized hospital. Methods: Hospital-based cross-sectional study was conducted among 481 study participants using systematic random sampling methods. The data were collected through a pre-tested structured interviewer-administered questionnaire. Bivariable and multivariable binary logistic regression was implemented. Finally, the odds ratio with a 95% confidence interval was calculated and a p-value < 0.05 was declared as significant. Result: The prevalence of low birth weight was 12.5 % (95% CI; 9.8, 15.7%). Preterm birth (AOR=38; 95% CI: 15.3, 93.0), pregnancy-induced hypertension (PIH) (AOR=2.6; 95%CI: 1.1, 6.4), maternal body mass index (BMI) <18.5kg/m2 (AOR=6.8; 95% CI: 1.5, 31.1), and grand multiparity (AOR=4.2; 95% CI: 1.2, 16) were positively associated with low birth weight. However, babies delivered from mothers with age >35 years (AOR=0.14:95% CI 0.03, 0.7) had lower odds of low birth weight. Conclusion: The prevalence of low birth weight in this study was higher than in the previous studies. The study revealed preterm birth, PIH, BMI <18.5 kg/m2, and grand multiparity were independent factors that increase the low birth weight while maternal age >35 years reduces the low birth weight. Therefore, health care professionals should emphasize the early identification and management of women with PIH, tackling prematurity, and preventing maternal malnutrition through nutritional counseling as much as possible.